2010
DOI: 10.1001/archophthalmol.2010.143
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lymphatics in Ciliary Body Melanomas With Extraocular Extension

Abstract: To assess the functional significance of intraocular tumor-associated lymphatic vessels in ciliary body melanomas with extraocular extension. Methods: Twelve consecutive patients enucleated for a malignant melanoma of the ciliary body with extraocular extension and immunohistochemical presence of intraocular LYVE-1-positive and podoplanin-positive lymphatic vessels were examined for proliferation status and tumor invasion into tumor-associated lymphatics. Proliferating lymphatic vessels were identified using L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
0
20
1
2
Order By: Relevance
“…First, podoplanin þ /laminin À lymphatic vessels can be detected within the cornea, sclera, and intraocular space of globes enucleated after open globe injury. To our knowledge, following our studies on intraocular malignancies with extraocular extension, [16][17][18] this is the second evidence of secondary lymphangiogenesis into the physiologically alymphatic intraocular space. Secondly, the presence of these pathologic lymphatic vessels does not seem to be associated with the mechanism of trauma, anatomic site of the eye wall defect, and time interval between trauma and enucleation.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…First, podoplanin þ /laminin À lymphatic vessels can be detected within the cornea, sclera, and intraocular space of globes enucleated after open globe injury. To our knowledge, following our studies on intraocular malignancies with extraocular extension, [16][17][18] this is the second evidence of secondary lymphangiogenesis into the physiologically alymphatic intraocular space. Secondly, the presence of these pathologic lymphatic vessels does not seem to be associated with the mechanism of trauma, anatomic site of the eye wall defect, and time interval between trauma and enucleation.…”
Section: Discussionmentioning
confidence: 92%
“…1,12,15,19,20,24 Furthermore, malignant melanomas of the ciliary body can attract extraocular lymphatics into the physiologically alymphatic eye when extraocular tumor extension provides routes of entry through the sclera, which otherwise seems to be a natural barrier against the invasion of lymphatic vessels. [16][17][18] Our data suggested that in a similar manner, preexisting conjunctival and/or limbal lymphatic vessels can outgrow and proliferate into the eye if the eye wall is opened by trauma. The hypothesis that the intraocular lymphatics that we detected actually are invading rather than displaced preexisting conjunctival lymphatic vessels is supported by the following observations.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations